PENGARUH PENAMBAHAN FILTRAT ROSELLA (Hibiscus sabdariffa Linn) KE DALAM PENGENCER TRIS-KUNING TELUR TERHADAP KUALITAS SPERMATOZOA KAMBING KACANG (The effect of rosella filtrate suplementation in tris-egg yolk extender on sperm..... - Reynold Laos; Aloysius Marawali; Petrus Kune; Henderiana L. L. Belli; Kirenius Uly (JURNAL NUKLEUS PETERNAKAN, 2021)
The purpose of this study was to determinate the effect of adding various levels of roselle filtrate (RF) into tris-egg yolk diluents (T-EY) on the quality of kacang goat spermatozoa. Semen was collected twice a week using an artificial vagina method of three male goats. Fresh semen obtained was evaluated macroscopically and microscopically with a motility value of 80%, viability 86.58%, concentration of 2,099.40 milionspermatozoa cells/ml, and an abnormality of 2.83%. Then the fresh semen was diluted according to the treatment, namely T0 (T-EY 100%), T1 (T-EY 100% + RF 1%), T2 (T-EY 100% + RF 2%), T3 (T-EY 100% + RF 3%), T4 (T-EY 100% + RF 4%), T5 (T-EY 100% + RF 5%). The diluted semen was stored at 3-5C, and evaluation was carried out every 24 hours on the quality of the spermatozoa. The results showed that spermatozoa in T-EY diluent with the addition of 3% RF (T3) had a higher quality (T<0.05) compered to the other five treatments, namely the motility reached (42,99±2,19%), viability (49,30±2,24%), and abnormalities (4,012±0,49%) during 5 days of storage. The conclusion of this study is the addition of 3% roselle filtrate in tris-egg yolk diluent is the best level and is more effective in maintaining the quality of spermatozoa kacang goat.